Communication Styles, Importance of Congruence Communication - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Communication styles can be categorised in countless ways. This chapter presents one of the most important models. Aggressive, passive, or assertive behaviour can be described using important communication characteristics. Recognising these is important not only to help professionals identify them more easily, but also to highlight, through a few examples, the key importance of communication in the social integration and socialisation process of young people, as well as in terms of their subsequent turning into perpetrators or victims. The individual factors in this complex system of relationships influence each other both directly and indirectly. A similarly bidirectional mechanism of action appears in the assessment of the authenticity of communicational interaction.At the same time, the level of children’s communication skills – or their impairment or lack thereof – in itself influences the extent to which and the success with which they will be able to exercise their guaranteed children’s rights.Keywords: communication styles, assertive communication style, aggressive communication style, passive communication style, congruent communication, incongruent communication